Raporturile dintre statele Uniunii Europene în funcţie de consum - Ștefănescu, Maria Livia (Calitatea Vieții, 2017)
Considering 31 European countries, we analyzed in comparison the equivalent medium consume of an adult. The studied “consumes” have been found in the Eurostat data base for the years 2005 and 2010. Both in 2005 as in 2010, Romania was situated on the last place regarding the mean of equivalent consume expenses of an adult. Research showed that there are two distinct groups of European states: GI (low consume) and GS (high consume). Romania finds itself in the GI group of consume. Between 2005 and 2010, these two groups are comprising the same states, constantly, so the structure of the consume remains constant. The European mean of consume raised, in time. Though, in 2010, the standard variation of consume values of the analyzed countries, and the variation coefficient of consume have both diminished, in comparison with 2005. So for EU countries, there is a sigma type tendency of convergence (Monfort, 2008). This convergence phenomenon manifest itself in both groups (GI and GS), countries that are very different in the medium consume, and in the level of economic and social development. With some exceptions, there is a rise of the medium consume for the majority of the European countries, and this tendency is very well shown by the linear regression equation (Fig. 2). The hierarchies of the European countries regarding the medium consume are not “leveled”, but there are very close. Over time, we have a very high level of stability of the rapports among European countries. Romania is on the last place for both hierarchies. Starting from the rising rate of the consume from the year 2010, we gave a prognosis for Romania vis-à-vis its neighbouring countries, and for the evolution of the Romanian consume in comparison to the European mean value.